La dinámica de la inversión privada. El modelo del acelerador flexible en una economía abierta - Mendoza, Waldo (Pontificia Universidad Católica del Perú. Departamento de Economía, 2020)
This work explores a flexible accelerator model in an open economy. This presentation begins setting the optimal capital stock of the entrepreneur, to which the costs of altering the existing capital stock are integrated to its target level. In formal terms, it is discrete-time a dynamic model that allows to analyse the changes in the exogenous variables on the endogenous ones in the short-run or period of impact, the transition to stationary equilibrium, and the change between stationary equilibria. Moreover, the model allows to perform comparative dynamics; in other words, appraising the impact of the exogenous variables on the trajectory of endogenous variables.
Documento de trabajo; 490
Keywords: Inversión; Acelerador flexible; Estática y dinámica comparativa; http://purl.org/pe-repo/ocde/ford#5.02.00